1994
DOI: 10.1002/j.1460-2075.1994.tb06448.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent expression of helix-loop-helix factor HES-1 prevents mammalian neural differentiation in the central nervous system.

Abstract: In the developing mammalian central nervous system, neural precursor cells present in the ventricular zone determine their fate to become neurons or glial cells, migrate towards the outer layers and undergo terminal differentiation. The transcriptional repressor HES‐1, a basic helix‐loop‐helix (bHLH) factor structurally related to the Drosophila hairy gene, is expressed at high levels throughout the ventricular zone, but the level decreases as neural differentiation proceeds. Because of this negative correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
242
2
4

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 371 publications
(265 citation statements)
references
References 29 publications
17
242
2
4
Order By: Relevance
“…6). Previous reports have also observed that both overexpression of Hes1 and activated Notch signaling inhibits neuronal differentiation within the cortex (Ishibashi et al, 1994). We also found that the expanded progenitor zone observed in NICD Tg mice is coincident with expanded Sox2-immunopositive and nestin-immunopositive cells.…”
Section: Research Articlesupporting
confidence: 83%
“…6). Previous reports have also observed that both overexpression of Hes1 and activated Notch signaling inhibits neuronal differentiation within the cortex (Ishibashi et al, 1994). We also found that the expanded progenitor zone observed in NICD Tg mice is coincident with expanded Sox2-immunopositive and nestin-immunopositive cells.…”
Section: Research Articlesupporting
confidence: 83%
“…Further confirmation of the immature character of the VZ cells was provided by analysis of HES-1 (Sasai et al, 1992) and Pax-6 expression. Overexpression of HES-1 in the rodent neural tube causes delay or inhibition of differentiation (Ishibashi et al, 1994), whereas HES-1 loss of function results in premature differentiation of neural plate precursor cells (Ishibashi et al, 1995). We observed that HES-1 expression was upregulated in the ventricular zone of Shh-Tg mice (Fig.…”
Section: Ectopic Shh Expression Confers Mixed Dorsal-ventral Charactementioning
confidence: 64%
“…When RBP-Jbinding sites in the Hes1 promoter were disrupted, the complex cannot interact with the promoter and Hes1 upregulation was completely abolished (Fig 2, Hes1/RBP-J(-)). Since Hes1 and Hes5 are known to inhibit neuronal differentiation [10], the above data suggest that the two Hes genes may mediate Notch-induced inhibition of cellular differentiation.…”
Section: The Notch Pathway: Cleavage and Translocation Of Notchmentioning
confidence: 82%